2011
DOI: 10.4103/0970-0218.84131
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chikungunya in urban field practice area of a private medical college, Chennai

Abstract: Background:The outbreak of Chikungunya in India started during December 2005 with more than 11,00,000 cases. Many cases with symptoms suggestive of Chikungunya reported to our urban health-training centre. Hence this study was done to estimate the prevalence of Chikungunya, to study the common treatment-seeking behavior, control measures and the sequalae of Chikungunya by follow-up.Materials and Methods:This cross-sectional study was done in Anagaputhur an urban field practice area of our college. The study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
22
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 2 publications
9
22
5
Order By: Relevance
“…Similar observations were reported by other studies [9,10]. However, in a study which was conducted in an urban field practice area of a private medical college of Chennai and in an outbreak at Vellore, south India more females were affected than males [11,12]. The maximum number of cases was in the age group of 11-50 years.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar observations were reported by other studies [9,10]. However, in a study which was conducted in an urban field practice area of a private medical college of Chennai and in an outbreak at Vellore, south India more females were affected than males [11,12]. The maximum number of cases was in the age group of 11-50 years.…”
Section: Discussionsupporting
confidence: 74%
“…In another study, 77.7% of the affected persons sought treatment at private clinics and 18.4% took treatment at government health set ups [11].…”
Section: Resultsmentioning
confidence: 99%
“…This could be attributed to the increased vector abundance and activity during rainy season as observed in study and in previous investigations (Mavalankar et al, 2008;Suryawanshi et al, 2009;Balasubramaniam et al, 2011;Dwibed et al, 2011;Mohanty et al, 2013). The patients in the present study that exhibited fever and headache were observed to show the highest prevalence of CHIKV antibody which could be the major symptoms of CHIKV infection in this environment.…”
Section: Discussionsupporting
confidence: 64%
“…The males are usually engaged in occupations that may expose them to bites by the vectors. However, the present finding disagrees with the earlier reports (Balasubramaniam et al, 2011;Dwibedi et al, 2011;Mohanty et al, 2013). The difference may probably be as a result of difference in geographical location and presence of socio-economic factors that facilitated the breeding of Aedes vector in their study area.…”
Section: Discussioncontrasting
confidence: 57%
“…Convenient sampling method was used. Total sample size was 312, prevalence 22.3% were taken Balasubramaniam SM, et al [17] where level confidence 95% and 5% standard error.…”
Section: Methodsmentioning
confidence: 99%